Fuzzy Bang-Bang Relay Control of a Rigid Rotor Supported by Active Magnetic Bearings - Nagi F.H.; Inayat-Hussain J.I.; Ahmed S.K. (MDPI, 2023)
Adaptive control systems; Bang bang control systems; Computer circuits; Electric control equipment; Feedback control; Fuzzy logic; Magnetic bearings; Magnetism; Proportional control systems; Rotating machinery; Sliding mode control; Three term control systems; Two term control systems; Active Magnetic Bearing; Bang-bang; Bang-Bang control; Fuzzy logic controllers; Fuzzy-Logic; Non linear control; Proportional-integral-derivatives controllers; Rotating machine; Rotors dynamics; Unbalance forces; Controllers